Macrophage Phenotype in Kidney Injury and Repair - Meng, Xiao-Ming (Kidney Dis (Basel), 2015)
BACKGROUND: Glomerular and interstitial macrophage infiltration is a feature for both the acute and chronic kidney diseases. Macrophages have been shown to play a diverse role in kidney injury and repair. Thus, macrophages may be a key cell type in acute and chronic kidney injury and repair. SUMMARY AND KEY MESSAGES: During renal inflammation, circulating monocytes are recruited and then become activated and polarized. By adapting to the local microenvironment, macrophages can differentiate into different phenotypes and function as a double-bladed sword in different stages of kidney disease. In general, M1 macrophages play a pathogenic role in boosting inflammatory renal injury, whereas M2 macrophages exert an anti-inflammatory and wound healing (or profibrotic) role during renal repair. In this review, we highlight the phenotypic polarization of macrophages in renal diseases and dissect their distinct functions in renal injury and repair processes, respectively. Moreover, the current understanding of regulatory mechanisms on the phenotypic switch and macrophage-related therapy are also intensively discussed.